Effect Light-Intensity on Sleep Quality in Elderly - Putri, Adela Henri; Satino, Satino; Rifai, Akhmad; Widodo, Widodo (JKG (JURNAL KEPERAWATAN GLOBAL), 2023)
Background: Bedroom lighting is accused of being one of the factors causing changes in the quality of sleep in the elderly. Modifying the power of room lighting is an alternative to improving the sleep quality of the elderly. The aim of the study is to determine the effect of lighting intensity on the sleep quality of elderly. Methods: A quantitative study with a quasi-experimental control group design. Amount of sample is 40 responden and choosen used random sampling. Quality of sleep measure by Pittsburgh Sleep Quality Index (PSQI) and light-intensity measure used a luxmeter. the intervention group received lights with an intensity of 5, 10, 15, 20 watts, where the respondents were treated every day for 4 days with these light intensities. The Shapiro-Wilk test was used to test the normality of the data, while paired T test used to analyze the conditions before and after in the control and treatment groups. Independent sample t-test used to compare the sleep quality of the control and treatment groups. Results: There was no difference in sleep quality in the control group (0.15) between before and after the study, but there was a difference in sleep quality in the intervention group (0.00). There were differences in sleep quality between the control and treatment groups after the intervention was given (0.01). Conclusion: The intensity of the light has an effect on the sleep quality of the elderly, where the lower the intensity of the light, the better the quality of sleep. Elderly should sleep on level lighting intensity less than 5 watt.